Availability of evidence on cataract in low/middle-income settings: a review of reviews using evidence gap maps approach. Issue 11 (6th June 2016) - Virendrakumar, Bhavisha; Jolley, Emma; Gordon, Iris; Bascaran, Cova; Schmidt, Elena
Abstract : Background: Despite high-quality evidence being essential for planning and delivering eye health programmes, evidence on what works is relatively scarce. To address this need, we developed eye health Evidence Gap Maps (EGMs) with the first one focusing on cataract. These maps summarise, critically appraise and present evidence in a user-friendly format. This paper presents experiences of developing the cataract gap map and discusses the challenges and benefits of the process. Methods: Following a comprehensive search of relevant databases, we sifted and extracted data from all relevant reviews on cataract. Critical appraisal was conducted by two reviewers independently using Supported the Use of Research Evidence checklist and a summary quality assessment was shared with the authors for comments. Results: A total of 52 reviews were included in the map. The majority of the reviews addressed quality of clinical care (20) and types of treatment (18). Overall, 30 reviews provided strong evidence in response to the research question, 14 reviews showed weak or no evidence and in 14 reviews the results were inconclusive. 14 reviews were regarded as high quality, 12 were medium quality and 26 were graded as low quality. To verify the validity of the Supporting the Use for Research Evidence (SURE) checklist, studies were also appraised using the Scottish Intercollegiate Guidelines Network (SIGN) tool. Based on the κ statistics test, results showed excellent agreement between the two checklists ( K =0.79). Discussion: EGMs support policy makers and programme managers to make informed decisions and enable researchers to prioritise future work based on the most evident gaps on knowledge.